2002
DOI: 10.1002/ptr.1016
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial potential of two different Hypericum species available in India

Abstract: The antimicrobial activity of extracts of the leaves and stems of two different varieties of Hypericum was evaluated by the disc diffusion method. Petroleum ether, acetone, chloroform and methanol extracts of Hypericum mysorense and Hypericum patulum stems and leaves were investigated for their antimicrobial activity against six different strains of bacteria and fungi by the zone of inhibition method (ZIM). The results showed that both the stem and leaf extracts of both species have a very broad spectrum of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 12 publications
0
25
0
Order By: Relevance
“…Previous reports also showed that some Hypericum species growing in various regions of the world have a remarkably broad spectrum of antimicrobial activities (Herrera et al, 1996;Sokmen et al, 1999;Mukherjee et al, 2002;Rabanal et al, 2002;Dall'Agnol et al, 2003;Fenner et al, 2005). However, none of those studies were about the Hypericum species that were the subjects of the current study.…”
Section: Antimicrobial Activities Of Extractsmentioning
confidence: 94%
See 1 more Smart Citation
“…Previous reports also showed that some Hypericum species growing in various regions of the world have a remarkably broad spectrum of antimicrobial activities (Herrera et al, 1996;Sokmen et al, 1999;Mukherjee et al, 2002;Rabanal et al, 2002;Dall'Agnol et al, 2003;Fenner et al, 2005). However, none of those studies were about the Hypericum species that were the subjects of the current study.…”
Section: Antimicrobial Activities Of Extractsmentioning
confidence: 94%
“…Therefore, research into biologically active extracts and compounds from natural sources has been of great interest to scientists in an attempt to discover new sources for drugs that may be useful in combating infectious diseases. In recent years, a large number of studies dealing with antimicrobial screening of the extracts of medicinal plants have been reported (Sokmen et al, 1999;Keles et al, 2001;Erdogrul, 2002;Mukherjee et al, 2002;Rabanal et al, 2002;Dall'Agnol et al, 2003;Fenner et al, 2005;Ozturk & Ercisli, 2005;Salehi et al, 2005). Turkish native herbs from both natural and cultivated sources are being more widely used on a commercial scale in the food industry, in traditional medicine, and for their flavoring properties (Baytop, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Plant extracts from Hypericum mysorense, Hypericum hookerianum and Usnea complanta showed significant anti-viral efficacy in a study by Vijayan et al 6 We did a survey to evaluate patient satisfaction and patient reported (HSV infected) outcomes on efficacy and safety of herbal combination Hyperisince ® (manufactured by Biogetica ® see table 1 for ingredients; Hyperisince is licensed by Ayush as a Ayurvedic Treatment for Herpes and is marketed elsewhere as a herbal dietary supplement). Hyperisince ® is GMP certified and manufactured at Deltas Pharma Pvt.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, they develop resistance to many antimicrobial agents 1 . The reason for this high resistance to commonly used antimicrobial agents may not be unconnected with the worldwide and indiscriminate use in the environment 2 . In addition, these antimicrobials sometimes cause allergic reaction and immunity suppression.…”
Section: Introductionmentioning
confidence: 99%